Cisplatin induces programmed death-1-ligand 1(PD-L1) over-expression in hepatoma H22 cells via Erk /MAPK signaling pathway - Qin, X.; Liu, C.; Zhou, Y.; Wang, G. (Cellular and Molecular Biology, 2010)
Cisplatin has been widely used in cancer treatment. However, the prognosis of the cancer patients following chemotherapy has not been substantially improved and several different mechanisms could be involved. Clinically alternative strategies such as immunotherapy and their combinations with chemotherapy have being used. Cancer immunoresistance and immune escape are major obstacles in chemotherapy. However, the effects of cisplatin on the immune responses of cancer cells are not clear. In the present studies, we investigate the expression of immunoresistance moleculor PD-L1 (the negative regulator programmed death-1-ligand 1) on cisplatin-induced hepatoma H22 cells, which can interact with PD-1 on T cells to mediate cancer immunoresistance. Hepatoma H22 cells were treated with cisplatin in vivo or in vitro to analysis the expression of PD-L1 by flow cytometry (FACS). Erk1/Erk2 phosphorylation expressions were examined by western blotting. We demonstrated that cisplatin was able to induce H22 cell apoptosis and when the concentration less than IC50 cisplatin could up-regulate PD-L1 expression in hepatoma H22 cells. The optimal concentration of cisplatin for the highest expression of PD-L1 was 0.5 Î¼g/ml in vitro. Meanwhile, cisplatin could induce the phosphorylation of Erk1/2.The lack of effect during treatment with a specific MAPK pathway inhibitor PD98059, demonstrated that cisplatin-induced PD-L1 expression is dependent of Erk1/2 phosphorylation. Our studies reveal a potential link between chemotherapy and cancer immunoresistance. PD-L1 and its signaling pathway appear to be a potential therapeutic target for the cisplatin treatment of hepatoma.